Art 37 Basel : the Art show = Die Kunstmesse = La Foire d'art = La Mostra d'arte. - Exhibition. Art 37 Basel. Art Basel. 2006-06-14. 2006-06-18 (Basel Ostfildern-Ruit : Hatje Cantz Verlag Ostfildern-Ruit Messe Basel, 2006)
Abramovic, Marina ; Acevedo Velarde, Gabriel ; Adrian-Nilsson, Gösta ; Aitken, Doug ; Akakce, Haluk ; Aladogan, Eylem ; Albers, Josef ; Almond, Darren ; Andersson, Christian ; Andre, Carl ; Anselmo, Giovanni ; Araujo, Vasco ; Ardouvin, Pierre ; Arp, Hans (Jean) ; Asse, Geneviève ; Atkins, Anna ; Bacon, Francis ; Baer, Monika ; Baldessari, John ; Baltz, Lewis ; Barry, Robert ; Bartana, Yael ; Baselitz, Georg ; Basilico, Gabriele ; Baudrexel, Florian ; Baumeister, Willi ; Beck, Lawrence ; Beckmann, Max ; Beecroft, Vanessa ; Bell, Larry ; Bellmer, Hans ; Ben-Gal, Avner ; Beuys, Joseph ; Bianchini, Alexandre ; Bill, David ; Bill, Jakob ; Bill, Max ; Bircken, Alexandra ; Bochner, Mel ; Bock, John ; Boetti, Alighiero ; Bonillas, Iñaki ; Bonvicini, Monica ; Bool, Shannon ; Borland, Polly ; Bornstein, Jennifer ; Bouchet, Mike ; Bourgeois, Louise ; Bourke-White, Margaret ; Brannon, Matthew ; Breivik, Bard ; Bryan, Edgar ; Bul, Lee ; Bulloch, Angela ; Burdin, Anthony ; Buren, Daniel ; Burr, Tom ; Bury, Pol ; Butzer, André ; Cabrita Reis, Pedro ; Cain, Peter ; Calder, Alexander ; Calzolari, Pierpaolo ; Carron, Valentin ; Casebere, James ; Castellani, Enrico ; Chamberlain, John ; Charlton, Alan ; Christo & Jeanne-Claude ; Ciussi, Carlo ; Claydon, Steven ; Clegg & Guttmann ; Clemente, Francesco ; Close, Chuck ; Coignet, Jean-Gabriel ; Collins, Phil ; Colombo, Gianni ; De Cordier, Louis ; Cragg, Tony (Anthony) ; Craig-Martin, Michael ; Creed, Martin ; Curlet, François ; Currin, John ; Cytter, Keren ; Dadamaino ; Day, E.V. ; Deacon, Richard ; Dean, Tacita ; Decrauzat, Philippe ; Dias, Ligia ; Dibenedetto, Steve ; Dion, Mark ; Do-Ho, Suh ; Doig, Peter ; Dolven, Anne Katrine ; Doud, Tim ; Dubossarsky, Vladimir ; Dunham, Carroll ; Durant, Sam ; Durham, Jimmie ; etc.
Duits
Engels
Frans
Italiaans
boek